The Beveridge Report (letter) - Orbell, Albert
1943-01-13 1943 1940s 2 pages Founded 1864 Incorpororated 1895 THE NATIONAL ASSOCIATION OF MEDICAL HERBALISTS OF GREAT BRITAIN LTD. (By Guarantee) President: A. BARKER, F.N.A.M.H. Registered Office and Offices of COLLEGE OF BOTANIC MEDICINE: 17, NORTH STREET. BARKING, ESSEX. HARRY ORBELL. F.N.A.M.H. HON. SECRETARY. Telephone No.: Rippleway 3623. OBJECTS. To elevate and maintain the status of Medical Herbalism. To impose, by examination, a qualification of knowledge upon all herbal practitioners. To demand legal status of those practitioners so qualified. DEPARTMENTS. RESEARCH & ANALYTICAL: Principal: F. FLETCHER HYDE. Esq.. B.Sc. (1st Honours London)., and Mrs. Florence A. Hyde, B.Sc. (Honours London), co-operating with Mrs. B.M. Robinson, B.Sc.. Ph.C., M.P.S. F.W. Cope, M.N.A.M.H. ALBERT ORBELL, M.N.A.M.H. HON. TREASURER: H.R.G. SKELTON, F.N.A.M.H. 28, Broomhall Street, Sheffield 3, EDUCATION: Miss M. HEWITT, F.N.A.M.H. 61, Queens Street, Rushden, Northants. TECHNICAL PUBLICATIONS: Hon. Editor: R.T. PHILLIPS, F.N.A.M.H. 15, Market Street, Wigan, Lancs. VENDOR SECTION: W.T. HEWITT, J.P., F.N.A.M.H. 61, Queens Street, Rushden, Northants. HO/EC. 13th Jan., 1943. The President, T.U.C, Transport House, Smith Sq., S.W.1. Dear Madam, re The Beveridge Report. I have been directed by my Council to write you relative to the far-reaching effect that the above-mentioned proposals will have, should they be adopted in the manner laid down by the Report. Let me say at the onset that my Council is fully in accord with the fundamentals therein but is seriously concerned by the fact that no proposals have been made to embrace those competent systems of medicine which are at present unrecognised. Sooner or later this problem will have to be solved, and my Council is of the opinion that no finer opportunity is afforded for such a step than by inclusion in the Beveridge proposals of such systems of medicine as are worthy. We have no quarrel with Allopathy, but in view of the fact that Osteopaths, Naturopaths and Medical Herbalists occupy a very considerable sphere of activity in the maintenance of National health, it is due, if not overdue, for their positions to be regularised and embraced under National service. We write you asking for your support. Reference to the T.U.C. activities for many years reveals the fact that they also realise that allopathic medicine could be advantageously supplemented by other reputable systems. Under 292/150.5/5/210